EFFECT OF DIFFERENT DIETARY PROTEIN LEVELS ON TESTOSTERONE AND TESTICULAR PARAMETERS IN AWASSI LAMBS - AL-DOSKI, SHAKER HASSAN (Journal of Duhok University, 2022)
This study aimed to investigate the effect of three different dietary protein levels on testosterone concentrations and testicular parameters in Awassi male lambs. Fifteen weaned Awassi ram lambs were randomly divided into three different dietary protein levels, 13% crude protein (T1), 14% crude protein (T2), and 15% crude protein (T3), with an equal energy level (12.1 MJ/kg/DM) for all treatments. The lambs were fed daily on concentrate ad libitum with access to fresh water. During the experimental period (75 days), all lambs were weighed weekly. Live weight and testicular parameters, as well as the serum testosterone concentrations were measured. The results showed that the dietary protein levels significantly increased (P < 0.001) lambs body weight in both T3 and T2 compared to T1. Although there were no differences found in relative weight of the testicle to lambs live weight, the dietary protein significantly increased (P < 0.05) testicular weight (110.83g ± 5.05, 135.32g ± 11.10 and 159.04g± 17.94) for T1, T2 and T3 respectively. There were high significant (P < 0.001) effects of protein diet noticed on the serum testosterone concentrations (0.46 ± 0.05, 4.70 ± 1.21 ± 1.03 and 4.24 ng/ml) for T1, T2 and T3 respectively. There were significant differences observed in right (P < 0.05) and left (P < 0.05) testicular parameters, whilst there were no effects of protein diet observed in both right and left epididymis between groups. The results indicated that the dietary protein levels positively affect in live body weight and reproductive activity of growing awassi lambs